2017
DOI: 10.1039/c7ra10499e
|View full text |Cite
|
Sign up to set email alerts
|

Dual redox-responsive PEG–PPS–cRGD self-crosslinked nanocapsules for targeted chemotherapy of squamous cell carcinoma

Abstract: A multifunctional branched copolymer, PEG–PPS–cRGD, was designed for developing dual redox-responsive self-crosslinked nanocapsules for targeted chemotherapy of squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The four-arm PEG-PPS-cRGD copolymer was synthesized via three steps according to our previous work. 36 Furthermore, 4 mg of ICG, 2 mg of DOXÁHCl and 4.5 mL of triethylamine (TEA) were dissolved in 0.4 mL of DMSO and mixed for 15 min with stirring. Additionally, 4 mL of PEG-PPS-cRGD aqueous solution (0.5 wt%) was slowly added to the ICG and DOX solution.…”
Section: Preparation and Characterization Of Dincsmentioning
confidence: 99%
“…The four-arm PEG-PPS-cRGD copolymer was synthesized via three steps according to our previous work. 36 Furthermore, 4 mg of ICG, 2 mg of DOXÁHCl and 4.5 mL of triethylamine (TEA) were dissolved in 0.4 mL of DMSO and mixed for 15 min with stirring. Additionally, 4 mL of PEG-PPS-cRGD aqueous solution (0.5 wt%) was slowly added to the ICG and DOX solution.…”
Section: Preparation and Characterization Of Dincsmentioning
confidence: 99%
“…(c) DOX concentrations in various organs and tumor tissue. Source: Reproduced with permission from Zhang et al (2017). Copyright 2017, The Royal Society of Chemistry…”
Section: Therapeutic Applications Of Cpncsmentioning
confidence: 99%
“…Moreover, studies have shown that enhanced tumor‐specificity and efficacy of DOX‐loaded CPNCs can be achieved by incorporating targeting moieties onto the surface of such nanocarriers. In the study of Zhang et al, cRGD peptide was used as the targeting moiety because it is able to interact with α v β 3 surface integrins typically overexpressed in squamous cells, and promote receptor‐mediated endocytosis (Zhang et al, 2017). The CPNC itself consists of a four‐armed, PEG‐poly(propylene sulfide)‐cRGD (PEG‐PPS‐cRGD) self‐crosslinked copolymer with DOX encapsulated via a solvent‐antisolvent method (Figure 3a), having an average diameter of 255 nm and 3.6 wt% DOX loading.…”
Section: Therapeutic Applications Of Cpncsmentioning
confidence: 99%
“…To date, various stimuli-responsive components, which are responsive to acidity, redox substances, enzymes, and light, have been extensively utilized to design polymer nanocarriers, aiming at the enhancement of the drug delivery efficiency to the cytoplasm or nucleus of cancer cells [21,22,23,24,25]. Reduction-responsive polymer nanocarriers based on disulfide bonds hold great promise for anticancer drug delivery because the intracellular fluid of cancer cells has a high concentration of glutathione (GSH) reducing agents, which can effectively divide the disulfide bond and break the polymer structure, thus resulting in a quick release of the loaded drugs [26,27,28].…”
Section: Introductionmentioning
confidence: 99%